Backyard poultry: legislation, zoonoses and disease prevention. (11th August 2014) - Whitehead, M. L.; Roberts, V.
<x xml:space="preserve">Abstract</x> In law, backyard poultry are "food‐producing animals" and "farmed animals" and are subject to regulations regarding welfare, prescribing, banned procedures, disposal of carcases, feeding bans, notifiable diseases and disease surveillance in addition to those applying to most other pets. Many owners and some veterinary surgeons are unclear about the requirements of these regulations. Backyard poultry are also associated with some different zoonotic disease risks to mammalian pets. Because a high proportion of poultry morbidity and mortality relates to infectious diseases, the health of backyard poultry is amenable to improvement through basic husbandry, biosecurity, hygiene and preventive medicine measures that can be incorporated into a simple "flock‐health plan". This article reviews these topics.